2012
DOI: 10.5005/jp-journals-10024-1207
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tumor Marker CA 125 in Saliva of Normal and Oral Squamous Cell Carcinoma Patients: A Comparative Study

Abstract: Background The mortality and morbidity associated with oral squamous cell carcinoma (OSCC) can be greatly reduced if tumor markers which can detect OSCC at an early stage are available. The use of saliva as an alternative to blood could provide a substantial advantage in sampling convenience. Cancer antigen 125 (CA 125) is a tumor-associated antigen found to be increased in epithelial tumors like oral, breast and ovarian cancers. Aim To determine whether salivary CA 125 levels are increased significantly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 15 publications
1
34
0
1
Order By: Relevance
“…Our study identified new mutations in these molecules and also discovered increased copy number of MUC2, MUC4 and MUC6. A few other studies have reported an association between elevated MUC16 level and progression of oral squamous cell carcinomas and thyroid neoplasm272829. In addition to the mucins, SIRPA displayed somatic mutations, copy number gain and corresponding overexpression in the progressive stages of this subject and the majority of the additional HPVOPC subjects analyzed.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our study identified new mutations in these molecules and also discovered increased copy number of MUC2, MUC4 and MUC6. A few other studies have reported an association between elevated MUC16 level and progression of oral squamous cell carcinomas and thyroid neoplasm272829. In addition to the mucins, SIRPA displayed somatic mutations, copy number gain and corresponding overexpression in the progressive stages of this subject and the majority of the additional HPVOPC subjects analyzed.…”
Section: Discussionmentioning
confidence: 61%
“…The highest frequency of somatic mutations spanning the coding regions (CDS) was observed in a panel of genes involved in various pathways associated with malignant progression23242526272829. These molecules include MUC16 (A.k.a.…”
Section: Resultsmentioning
confidence: 99%
“…Also the levels salivary CA-125 were seen to be reduced significantly postoperatively in patients of group 5 (888.15 mg/dl) as compared to patients with oral malignancy in group 4 (1362.2 mg/dl) Balan et al [13] in a similar study observed the mean salivary CA 125 values of OSCC patients as 320. 25 and that of control group as 33.14 (p<0.05).…”
Section: Variablesmentioning
confidence: 80%
“…The resulting supernatant fluid was subjected to ELISA for assessment of CA 125 and LDH levels. [13] Statistical analysis: The collected data was coded and entered in Microsoft Excel sheet. Mean, SD and Median was calculated for quantitative data.…”
Section: Methodsmentioning
confidence: 99%
“…CA 125 is a tumor associated antigen which is found to be elevated in the serum and saliva of patients with oral, breast, and ovarian tumors [43]. …”
Section: Potential Biomarkers In Salivamentioning
confidence: 99%